Analisis Deskriptif Indeks Pembangunan Manusia Indonesia Periode Tahun 2020 - 2023 - Ummah, Sapinatul (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Human development is one of the national development goals outlined in Law Number 25 of 2004 concerning the National Development Planning System. The Human Development Index (HDI) serves as a key indicator to measure the success of human development, comprising three dimensions: longevity and healthy life, knowledge, and a decent standard of living. During the period 2020-2023, Indonesia's HDI experienced an improvement. In 2023, Indonesia's HDI reached 74.39, a rise of 0.62 points (0.84 percent) compared to the previous year (73.77). This increase was observed across all dimensions, including longevity and healthy life, knowledge, and a decent standard of living. The objective of this research is to provide a descriptive analysis of Indonesia's HDI during the period 2020-2023. Secondary data from the Central Statistics Agency (BPS) were utilized, encompassing HDI data, life expectancy, years of schooling expectancy, and per capita expenditure per year. The research findings reveal a significant improvement in Indonesia's HDI during the 2020-2023 period. The HDI increase is evident in all dimensions: 1) Longevity and Healthy Life Dimension, Life expectancy at birth increased from 73.7 years in 2020 to 73.93 years in 2023. 2) Knowledge Dimension, Years of schooling expectancy rose from 12.6 years in 2020 to 12.8 years in 2023. 3) Decent Standard of Living Dimension, Per capita expenditure per year increased from Rp11,293,000 in 2020 to Rp11,899,000 in 2023.